An investigation of hydraulic fracturing initiation and location of hydraulic fracture in preforated oil shale formations - Lianghao Zhai; Yang Xun; Huanan Liu; Bo Qi; Jinghua Wu; Yafei Wang; Chen Chen (Scientific Reports)
Abstract Horizontal well fracturing technology enables the commercial production of low-permeability reservoirs, with perforation fracturing technology serving as a critical component of multistage fracturing for horizontal wells. However, the presence of the horizontal wellbore and the perforation borehole significantly complicates the distribution of the local stress field. The extension behavior of hydraulic fractures cannot be accurately described. The mechanisms of initiation and extension of fractures resulting from perforation fracturing require further investigation. By employing the principle of superposition and considering the effects of far-field stress, fluid pressure within the wellbore, filtration loss of fracturing fluid, and temperature variations, the distribution of the stress field around the perforation has been elucidated. A theoretical model for calculating hydraulic fracture initiation pressure and location was developed based on the stress distribution pattern and the established rock damage criterion for various rock types. The accuracy of this theoretical model was validated through real triaxial hydraulic fracturing experiments. A combination of theoretical calculations and perforation fracturing experiments revealed that the fracture initiation location for perforation fracturing occurs at the intersection of the perforation borehole and the horizontal wellbore. Moreover, a comprehensive fracturing calculation guideline was proposed for varying fracturing conditions by comparing the theoretical and experimental values of fracture initiation pressure. The findings presented in this paper are anticipated to enhance the prediction of hydraulic fracture initiation pressures and locations in perforation fracturing.